1993
DOI: 10.1037/1040-3590.5.2.131
|View full text |Cite
|
Sign up to set email alerts
|

The Pre-School Activities Inventory: A standardized assessment of gender role in children.

Abstract: The PreSchool Activities Inventory (PSAI) is a new psychometric scale for the assessment of gender role behavior in young children. Its design and test specification are reported, and the piloting and item analysis are described. Evidence of reliability is given, and several validation studies are reported, as are data on age standardization and norming. Some applications of the PSAI are considered. A number of studies have demonstrated that children show gender-stereotyped toy and activity choices from as ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
178
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(182 citation statements)
references
References 24 publications
2
178
2
Order By: Relevance
“…In previous research with adult populations, the sex difference in PSAI scores has generally shown a very large effect size (d = 2.65-3.25) (Alexander, 2006;Hines et al, 2003). The PSAI also shows moderate test-retest reliability for each sex (boys -r = .62, girls -r = .66) and moderate to high split-half reliability for each sex (boys -r = .66, girls -r = .80) (Golombok & Rust, 1993). In addition, PSAI scores correlate moderately with teacher ratings of gendered behavior (boys -r = .37, girls -r = .48) (Golombok & Rust, 1993).…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…In previous research with adult populations, the sex difference in PSAI scores has generally shown a very large effect size (d = 2.65-3.25) (Alexander, 2006;Hines et al, 2003). The PSAI also shows moderate test-retest reliability for each sex (boys -r = .62, girls -r = .66) and moderate to high split-half reliability for each sex (boys -r = .66, girls -r = .80) (Golombok & Rust, 1993). In addition, PSAI scores correlate moderately with teacher ratings of gendered behavior (boys -r = .37, girls -r = .48) (Golombok & Rust, 1993).…”
Section: Methodsmentioning
confidence: 84%
“…The PSAI also shows moderate test-retest reliability for each sex (boys -r = .62, girls -r = .66) and moderate to high split-half reliability for each sex (boys -r = .66, girls -r = .80) (Golombok & Rust, 1993). In addition, PSAI scores correlate moderately with teacher ratings of gendered behavior (boys -r = .37, girls -r = .48) (Golombok & Rust, 1993).…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The Bem Sex-Role Inventory (BSRI; Bem, 1981), the Pre-School Activities Inventory (PSAI; Golombok & Rust, 1993), and the Occupation, Activities, and Traits-Attitudes and Personal Measure (OAT-AM and OAT-PM; Liben & Bigler, 2002) measured typical gender role behavior. Briefly, the BSRI consists of 60 items and two scales measuring psychological masculinity (e.g., "independent" and "assertive") and femininity ("affectionate" and "softspoken"), such that higher scores on a scale indicate a stronger endorsement of that personality dimension.…”
Section: Behavioralmentioning
confidence: 99%
“…The collection of normative statistics provides data for the testing of the validity of the instrument (Cicchetti, 1994), determines the effectiveness of the instrument to discriminate between the target and normal populations (Golombok & Rust, 1993), and increases the robustness and reliability of the measurement (Friedrich, Gramsch, Damon, Hewitt, Koverola, Lang, Woplfe, & Broughton, 1992). Discriminant validity provides a context for the interpretation of scale scores (Malic, Ivnik, Smith, Tangalos, Peterson, Kokmen, & Kurland, 1992;Sharma, Botzet, Sechrist, Arthur, & Winters, 2006), and enables researchers and practitioners to make meaningful and valid interpretations of within-and betweengroup comparisons (Apolone & Masconi, 1998;Cicchetti;Cooke, et al, 2006;Gandek & Ware, 1998;Golombok & Rust).…”
Section: The Trauma Play Scalementioning
confidence: 99%